2021
DOI: 10.1002/cncr.33497
|View full text |Cite
|
Sign up to set email alerts
|

Early radiotherapy preserves vision in sporadic optic pathway glioma

Abstract: BACKGROUND Sporadic optic pathway/hypothalamic gliomas represent a unique entity within pediatric low‐grade glioma. Despite favorable survival, location makes treatment difficult and local progression debilitating. This study is a longitudinal assessment of visual acuity (VA) among children treated within the last 2 decades. METHODS Clinical characteristics were abstracted for patients treated from 2000 to 2018 at Texas Children's Cancer Center in Houston. Ophthalmologic data taken at 3‐ to 6‐month intervals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The decline occurred within the first 2 years after RT and was not related to progression of disease [ 16 ]. Recently, Hanania et al [ 26 ] reported that early PBT as an initial or first-line salvage treatment was related to improved 8-year blindness-free survival rate of 100% compared to a 60% rate following chemotherapy. In this report, the visual outcomes of late PBT were not different from those of no PBT.…”
Section: Late Effects Following Rt For Opgmentioning
confidence: 99%
“…The decline occurred within the first 2 years after RT and was not related to progression of disease [ 16 ]. Recently, Hanania et al [ 26 ] reported that early PBT as an initial or first-line salvage treatment was related to improved 8-year blindness-free survival rate of 100% compared to a 60% rate following chemotherapy. In this report, the visual outcomes of late PBT were not different from those of no PBT.…”
Section: Late Effects Following Rt For Opgmentioning
confidence: 99%